Blast Performance of Reinforced Concrete Columns Protected by FRP Laminates - Kadhom, Bessam (Université d'Ottawa / University of Ottawa, 2016)
Recent terrorist attacks on critical infrastructures using car bombs have heightened awareness on the needs for blast resistance of structures. Blast design of civilian buildings has not been a common practice in structural design. For this reason, there is now an urgent need to mitigate the potentially devastating effects of blast shock waves on existing structures. The current research project, the results of which are reported in this dissertation, aims to expand knowledge on blast resistance of reinforced concrete building columns, while developing a technology and design procedure for protecting critical buildings columns against the damaging effects of impulsive blast loads through the use of externally applied fibre-reinforced polymer (FRP) jackets of different material architecture. The research project has a significant experimental component, with analytical verifications. A total of thirty two reinforced concrete columns were experimentally investigated under the effects of simulated blast loads using the University of Ottawa Shock Tube. Column dimensions were 150 mm x 150 mm in cross section and 2438 mm in length. Each concrete column was reinforced longitudinally with four 10M rebars which were tied laterally with 6.3 mm closed steel hoops, spaced at 37.5 mm and 100 mm c/c, representing seismic and non-seismic column details, respectively. The experimental research had two phases. Phase-I (sub-study) included blast tests of eight as-built, seismically detailed columns. The behaviour of these columns was explored under single and multiple blast shots, with and without the application of pre-blast axial loads. Phase-II (main-study) included column tests of different carbon FRP (CFRP) designs to investigate the significance of the use of different CFRP column jacket designs on dynamic response of twenty four seismic and non-seismic RC columns. Analytical investigation was conducted to assess and verify the significance of experimentally investigated parameters on column response. These included the use of Single-Degree-of-Freedom (SDOF) dynamic inelastic analysis, generation of dynamic resistance functions, the effects of variable axial loads, different plastic hinge lengths and the influence of secondary moments (P- moments) on column behaviour. The results indicate that the loading history has effects on column response, with multiple shots reducing column stiffness, and affecting dynamic response of columns relative to single blast shots of equivalent magnitude. The effect of concrete strength within the normal-strength concrete range is to increase strength and decrease deformations. Columns with CFRP jackets have considerable improvements in column deformability, with additional increases in column strength. The CFRP laminate design influences performance, with jackets having fibres in ±45o orientation especially improving column ductility and increasing plastic hinge lengths, thereby permitting redistribution of stresses and dissipating blast energy. Axial gravity loads vary during blast loads and can affect column strength. It was shown that SDOF dynamic inelastic analysis does capture key structural performance parameters in blast analysis. The consideration of experimentally observed parameters in column analysis; including the influence of CFRP design and associated change in plastic hinge length, variable axial load during response, and secondary moment (P- moments) result in significant improvements in the accuracy of blast analysis. The experimental results and the suggested improvements to the SDOF analysis technique can be used to implement a performance-based design approach recommended as part of the current research project for design of CFRP protection systems for concrete columns.This research project was conducted jointly by the National Research Council Canada (NRC) and the University of Ottawa.
Keywords: Blast loads; FRP Laminates; RC columns; Shock tube